Development and evaluation of an emulsion containing lycopene for combating acceleration of skin aging - Letícia Caramori Cefali; Tatiana Maria Souza-Moreira; Marcos Antônio Corrêa; Hérida Regina Nunes Salgado; Vera Lucia Borges Isaac (Universidade de São Paulo, 2015)
Lycopene, a carotenoid and potent antioxidant is found in large quantities in tomatoes. Lycopene combats diseases, such as cardiovascular disease and different types of cancer, including prostate cancer. However, its topical use in emulsion form for the combat of skin aging is under-explored. The aim of the present study was to develop an emulsion containing lycopene extracted from salad tomatoes and evaluate its cytotoxicity, stability, rheological behavior, antioxidant activity and phytocosmetic permeation. The developed cosmetic comprised an oil phase made up of shea derivatives and was evaluated in terms of its physiochemical stability, spreadability, thermal analysis, rheological behavior, microbiological quality, cytotoxicity, antioxidant activity, cutaneous permeation and retention. The results demonstrate that this phytocosmetic is stable, exhibits satisfactory rheological behavior for a topical formula and is a promising product for combating skin aging.